Development of two infant formulas as an economic and healthy alternative for help to food security and nutritional security to the infant population - López-Marín, Beatriz Estella; Álvarez-Rivera, Julie Maritza; Carvajal de Pabón, Luz Marina (Universidad y Salud, 2016)
Introduction: When breastfeeding is not feasible, other sources to provide the required nutrients to babies are sought, such as infant formulas that comply with current regulation and with the baby’s growth requirements. Objective: To design two liquid infant formulas that provide daily macronutrients and some micronutrients (folic acid, zinc, calcium, and iron) requirements, based on low-cost pasteurized cow milk in order to be more affordable for vulnerable babies and to contribute with their growth. Materials and Methods: Exploratory study developed in two phases: Formulation and preparation of the infant formula and verification of its efficacy in terms of babies’ growth. Results: The infant formulas comply with all manufacturing requirements, are inexpensive, and appropriate to sustain normal growth, according to WHO. Conclusion: The two infant formulas developed have adequate macronutrient and micronutrient contribution with sensorial and microbiological characteristics that comply with local and foreign regulations, are inexpensive, and appropriate to sustain babies’ normal growth.